Soil Aggregate Stability in Salt-Affected Vineyards: Depth-Wise Variability Analysis - Aplena E. S. Bless; François Colin; Armand Crabit; Stéphane Follain (Land, 2022)
Soil aggregate stability is an ideal integrative soil quality indicator, but little is known about the relevance of such an indicator with soil depth for salt-affected soils. The objective of this study was to determine soil aggregate stability and identify preponderant aggregation factors, both in topsoil and subsoil horizons in salt-affected conditions. We conducted field investigations by describing soil profiles in pedological pits and by collecting soil samples from different field units. Soils were sampled within different soil horizon types, from superficial tilled organo-mineral horizons to mineral horizons. For all soil samples, we determined the mean weight diameter (MWD) as an indicator of soil aggregate stability and also determined associated physical and chemical properties in some samples. The measured MWD value from 0.28 mm to 1.10 mm could be categorised as unstable, with MWD values and variability decreasing drastically from the topsoil to the deepest mineral horizons. Analysis of MWD in relation to physical and chemical properties suggested that the variability in the MWD value of A-horizons was influenced by both clay fraction abundance and soil organic carbon (SOC) content and the nature of the agricultural practices, while at deeper B-horizons, the decrease in SOC content and the variability in other soil properties with soil depth could be used to explain the overall low aggregate stability. In this study, investigations of soil pits coupled with measurements of soil aggregate stability indicated that it could be possible to restore soil structure quality by limiting deep soil profile compaction in order to improve salt leaching and exportation.